Subscription Inventive Over the S-Convex Set in Linear Space (Indian Journal of Advanced Mathematics (IJAM), 2025)
In the context of the present paper, our focus revolves around the exploration and analysis of S-convex sets, which represent a fascinating and novel extension of the classical concept of convex sets. We define S-convex sets and discus their main properties as well as the corresponding S-convex hull. Moreover, we clarify the concept of S-linear combinations, which are essential to our research. This first work lays the foundation for a thorough study of S-convex sets and their characteristics. A number of examples are included to show the necessity of the hypotheses of various theorems.